Bodysnatching in the marketplace: Market-focused health activism and compelling narratives of dys-appearance. (September 2018) - Cronin, James; Hopkinson, Gillian
This article theorizes how market-focused health activism catalyses market change through revealing the ill-effects that consumers' conformity with market-shaped expectations and ideals has on their bodies and embodied lives. An understanding of this activism is developed by analysing a vicarious form of 'bodily dys-appearance' which is used in Jamie Oliver's televised documentary, Sugar Rush (2015), to narratively provoke corporeal anxieties among audiences. In our analysis, we borrow tropes from the science fiction film, Invasion of the Body Snatchers, to interpret themes centred on a threat, a victim and a hero. We argue that market-focused health activism problematizes the neo-liberal logic of personal responsibility and promotes market intervention as the only means to insulate and safeguard the body from harm. Where extant theorization of consumers' antagonism towards the market hinges mostly on politically or intellectually motivated resistance, this article demonstrates how somatically oriented concerns operate alternatively to invoke activism.